علامہ محمد اقبال کا تصور خودی اور مسلمانان برصغیر: ایک تحقیقی جائزہ: Allama Muhammad Iqbal’s Philosophical Concept of Self (Khudī) and Muslims of India: A Research Study (Al-Qamar, 2021)
The great Iqbal is one of the most prominent Muslim philosophers of the twentieth century and his thoughts are the guideline for the Muslims of India not only but the entire world. Among his different concept of the society his concept the self is also pushed the Muslims towards glory. He   gave lesson of self and called it a key of success for the Muslims of India. Iqbal advises the Muslim world to be steadfast instead of getting into trouble and forbids them from accepting slavery. In his view, the existence of the self is more important for human action. While in this paper it has tried to highlights the thematic concept of Khudī (self).
Keywords: Iqbal; Philosophy; Muslims; India; Self; Israr-e-Khudī